Effects of Elevated Ozone Levels on Photosynthesis, Biomass and Non-structural Carbohydrates of Phoebe bournei and Phoebe zhennan in Subtropical China - Chen, Zhan; Cao, Jixin; Yu, Hao; Shang, He (Frontiers in Plant Science, 2018)
To assess the impacts of ozone (O3) on carbon metabolism of subtropical broadleaved tree species, seedlings of Phoebe bournei and Phoebe zhennan were exposed to elevated O3 levels in open-top chambers (OTCs) from June to November 2014. Three treatments were conducted in nine total OTCs, including charcoal-filter air (CF) as a control treatment, low O3 treatment ‘O3-1’ (~100 nl l-1), and high O3 treatment ‘O3-2’ (~150 nl l-1). Our findings demonstrated that elevated O3 levels significantly decreased the net photosynthesis rates (Pn) and leaf, root, and total biomass of both species, while it did not significantly affect the root/shoot ratio in P. bournei and P. zhennan. O3-1 treatments significantly increased water soluble carbohydrates (WSC) in leaves of both tree species, while only increased the total nonstructural carbohydrates (TNC) and starch in leaves of P. bournei; effects on P. zhennan were equivalent in comparison to the control treatment (CF). Likewise, there was no effect of treatment on the polysaccharide content of both tree species. The contents of polysaccharide, starch contents in fine roots of both species, and TNC in fine roots of P. bournei increased significantly in O3-1 compared to CF. O3-2 treatment significantly decreased starch and TNC in the fine roots of P. bournei, and significantly decreased polysaccharide, starch, WSC and TNC in the fine roots of P. zhennan. Elevated O3 had no effects on leaf polysaccharide in both species, but O3-1 significantly increased polysaccharide in the fine roots of both species, and O3-1 significantly increased WSC in the leaves while decreased that in the fine roots of both species. These results suggested that elevated O3 levels have significant impacts on the carbon metabolism of both tree species in our study, with differential responses between tree species and among leaves and roots.